Feasibility analysis of Fischer‐Tropsch synthesis tail gas as a fuel for solid oxide fuel cells. (25th March 2022) - Wei, Keyan; Yue, Shuai; Hou, Xiangjun; Jiang, Yao; Jiang, Cairong; Yao, Yali; Yin, Jie; Ma, Jianjun
Summary: The tail gas of Fischer‐Tropsch synthesis (FTS) contains unconverted syngas and gaseous hydrocarbons. It is usually treated at a high‐cost and low‐efficiency method, whereas it is a feasible fuel for solid oxide fuel cells (SOFCs). Herein, we evaluated the carbon deposition temperature of the FTS tail gas obtained at various reactor pressures. Thermodynamic calculation showed that the FTS tail gas could be used in SOFCs without the risk of carbon deposition. By adding 5% water, the initial non‐carbon deposition temperature was dropped from 830°C (without water co‐feeding) to 720°C. Under reforming, the syngas (H2 /CO) ratio is about 2 when it reaches equilibrium states, which can be recycled back into the FTS process. Theoretically, a current of 6.5‐7.1 A per 100 mL FTS tail gas could be generated by the SOFC. This study demonstrates that it is promising to use the FTS tail gas as a carbon‐containing fuel for SOFCs. Highlights: A new concept of the utilization of FTS tail gas as a fuel in a SOFC is developed. FTS tail gas can convert to syngas with H2 /CO = 2 that can be recycled back into FTS. Co‐feeding water into FTS tail gas reduces the non‐carbon deposition temperature. Theoretical current densities proved the FTS tail gas is a promising fuel for SOFCs. Abstract : The Fischer‐Tropsch synthesis (FTS) tail gas was evaluated as a fuel in solid oxide fuel cells (SOFCs) by estimating the carbon deposition temperature without a risk of carbon deposition when the SOFC temperature is below 830°C. A high current of 6.5‐7.0 A was achieved by feeding 100 mL FTS tail gas. Under reforming, the syngas (H2 /CO) ratio is about 2 when it reaches equilibrium states, which can be recycled back into the FTS process.